(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
أثبتت هذه الدراسة من خلال التحرّيات الحقلية ومعطيات الدراسة الهيدروجيولوجية أنّ مصدر مياه الينابيع والاّبار الرئيسة في منطقة قرى القطيلبية ،هي الصّخور الرسوبية العائدة لحوامل مائية ، تعود لتشكيلات طابقي الألبيان والسينومانيان الأسفل والأوسط من دور الكريتاسي، إذ تشكّل صخور السينومانيان الحامل المائي الرئيس في المنطقة. يتلاقى هذا الحامل مع الحامل المائي الجوراسي عند الارتفاع الطبوغرافي 75م (حدود فالق السن) ، ممّايجعل المناطق الغربية لمنطقة الدراسة مأمولة من حيثُ احتواؤها على غزارة من المياه الجوفية. تشير منطقة تلاقي الحاملي على تغذّي نبع السّن على مياههما، ممّا يفسّر التصريف العالي لهذا النّبع. This study confirm, from field work and hydro geological study data, that the water of main springs and wells source in Al Qutailibiyah area are coming from sidementry rock aquifers which belong to albian and lower- middle cenomanian formations. Cenomanian rocks are the main aquifer in this area. This aquifer cross by jurrasic nearby topographic altitude 75m (AL-Sen fault zone). This suction makes The western side of study area more hopes with ground water existence. This area support Al-Sen spring which explain the high drainage of it.